A META-SYNTHESIS OF VIRTUAL REALITY IN LEARNING IN INDONESIA - Andy Sapta; Abd Gafur; Ami Hibatul Jameel (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2023)
Abstract: This research was conducted in the form of a literature study. This study investigates the use of Virtual Reality (VR) in teaching, including VR methods and their application to learning. In the literature study, the database used comes from Garuda (Garuda Digital Reference), published by The Ministry of Education, Culture, Research, and Technology. The results of the literature study obtained data that 157 articles discuss the use of VR in learning from 2012 - 2022 and in the majority of VR development using the 3D Modeling method, as much as 43%. Overall, using VR in learning provides positive results that can improve learning outcomes. Three essential things must be considered in the development of VR, namely: (1) the cost of operating VR technology, (2) Accessibility that makes it easy for teachers and respondents to access the technology, (3) Setting up a virtual environment to create a practical learning experience for respondents.            Keywords: development; learning; virtual reality.  Abstrak: Penelitian ini dilakukan dalam bentuk studi literatur. Dalam penelitian ini, menyelidikan penggunaan VR dalam pembejaran, meliputi metode VR yang digunakan dan penerapannya pada pembelajaran. Dalam studi literature, basis data yang digunakan berasal dari Garuda (Garuda Rujukan Digital) yang dipublikasi oleh The Ministry of Education, Culture, Reseach, and Technology. Dari hasil studi literature diperoleh data bahwa terdapat 157 artikel yang membahas tentang penggunaan VR dalam pembelajaran dari tahun 2012 – 2022. Secara mayoritas pengembangan VR dengan menggunakan metode 3D Modelling, sebanyak 43%. Secara keseluruhan penggunaan VR dalam pembelajaran memberikan hasil yang positif dapat meningkatkan hasil belajar. Terdapat tiga hal penting yang harus diperhatikan dalam pengembangan VR, yaitu: (1) biaya pengoperasian teknologi VR, (2) Aksesibilitas yang memudahkan pengajar dan responden untuk mengakses teknologi tersebut (3) Menyiapkan lingkungan maya (virtual environment) agar menciptakan pengalaman belajar yang efektif bagi responden. Kata kunci: pembelajaran; pengembangan; virtual reality